MARKET ORIENTATION AND PRODUCT INNOVATION AS AN MSME MARKETING STRATEGY - Faerrosa, Lady; Athar, Handry Sudiartha; Widiana, Harmi (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
Marketing performance is one of the benchmarks for the company's success strategy. There are many factors that can affect the company's performance. This study aims to examine market orientation and product innovation on the marketing performance of culinary SMEs. Respondents in this study were culinary MSMEs with the ordinary types of processed foods throughout the city of Mataram, Indonesia. The sampling technique used is simple random sampling. The questionnaire containing 17 questions was distributed to all respondents. The data analysis technique used in this research is the multiple linear regression technique through the SPSS version 16.0 application for windows. The results of this study indicate that the level of market orientation and product innovation of respondents is relatively high, but only product innovation significantly affects marketing performance. On the other hand, market orientation is not proven to have an effect on marketing performance. However, market orientation and product innovation together can significantly affect marketing performance. Thus, the results of this research become the basis for carrying out business efforts and market-oriented strategies and increasing product innovation.